Artificial Intelligence in Photojournalism (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The advent of artificial intelligence (AI) technologies has brought profound changes to digital photography and photojournalism, presenting both valuable opportunities and significant challenges. The rise of AI-powered editing tools and image manipulation capabilities raises serious concerns about the authenticity of visual journalism, as altered images can easily contribute to misinformation and diminish public confidence in visual content. This study explores the evolving relationship between digital photography and photojournalism amid rapid AI advancements. Its goal is to investigate how AI integration is reshaping creative practices while introducing pressing ethical, professional, and industry-related issues that demand immediate consideration. The paper contends that gaining insight into these shifts is crucial for photographers and photojournalists to develop effective strategies for navigating the complexities of the digital age while safeguarding the authenticity and influence of their work. Employing a qualitative research approach, the study identifies major challenges such as the commercialization of imagery, the threat of visual misinformation, and the imperative for professionals to adapt their skills to an AI-influenced environment. It also underscores the potential benefits of using AI tools to optimize workflows, enrich storytelling, and boost audience engagement. Ultimately, the research emphasizes the importance for visual media practitioners to adjust to the changing landscape while maintaining ethical practices, nurturing creativity, and embracing innovation to succeed in a digitally driven media ecosystem.